2008
DOI: 10.1103/physrevlett.100.256401
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Description of Carrier Mediated Magnetism in Cobalt Doped ZnO

Abstract: Substitutional cobalt in ZnO has a weak preference for antiferromagnetic ordering. Stabilization of ferromagnetism is achieved through n-type doping, which can be understood through a band coupling model. However, the description of the transition to a ferromagnetic ground state varies within different levels of band theory; issues arise due to the density functional theory underestimation of the band gap of ZnO, and the relative position of the nominally unfilled Co t 2d states. We examine these limitations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 276 publications
(136 citation statements)
references
References 28 publications
8
128
0
Order By: Relevance
“…However, the large fraction of the Fock exchange α = 43% used in the exchange functional (which is necessary for reproducing the correct band gap of MAPbI 3 )15, 62 introduces too much localization for d electrons as showed by recent studies 68, 69, 70. Thus, the level of localization in the transition metal d states should be underestimated in PBE calculations and overestimated in HSE calculations.…”
Section: Computational Approachesmentioning
confidence: 97%
“…However, the large fraction of the Fock exchange α = 43% used in the exchange functional (which is necessary for reproducing the correct band gap of MAPbI 3 )15, 62 introduces too much localization for d electrons as showed by recent studies 68, 69, 70. Thus, the level of localization in the transition metal d states should be underestimated in PBE calculations and overestimated in HSE calculations.…”
Section: Computational Approachesmentioning
confidence: 97%
“…In order to investigate the magnetic coupling of Co 2+ ions in the vicinity of defects with a magnetic moment, a series of calculations was performed in which Zn 2+ ions at all unique sites close to V are all antiferromagnetic, as expected, 30,80 see Table VI). Chanier et al 81 obtain values of 16 and 6 meV for the total energy difference E using the LSDA+U method for near-neighbor Co 2+ ions in the same basal plane and in adjacent planes.…”
Section: E Role Of Transition-metal Impuritiesmentioning
confidence: 97%
“…Lany and coworkers 49 using DFT-GGA and DFT + nonlocal-external-potential (NLEP) methods found similar results to Walsh and coworkers. 30 They found that DFT in a GGA approximation predicts a weak antiferromagnetic interaction when there is one n-type carrier per Co ion pair and a strong ferromagnetic interaction (∼300 meV) for the DFT+NLEP calculation. The reason for the different behavior in the two methods is the predicted occupancy of the Co-3d levels, which are empty in the absence of n-type carriers.…”
Section: Comparison To Other Modelsmentioning
confidence: 99%
“…While there is an established system and property dependence of the amount of exchange required to yield accurate observables (Corà et al 2004;Walsh et al 2008), the HSE06 functional has demonstrated recent success and transferability in describing the structural, electronic and defect properties of semiconducting and insulating systems (Brothers et al 2008;Hummer et al 2009;Chen et al 2009a;Walsh et al 2009b). …”
Section: Methodsmentioning
confidence: 99%